Process Utility and the Effect of Inaction Frames - Evangelidis, Ioannis; Levav, Jonathan (Management Science, 2018)
We introduce a new type of utility that we call “process utility,” which pertains to individuals’ preference about how they want to obtain an outcome. We posit that decision makers derive utility not only from the outcome itself, but also from the process through which that outcome is obtained. We focus on two normatively equivalent processes for obtaining an outcome: action and inaction. We argue that inducing differences in how outcomes are obtained can lead to significant preference reversals. We examine process utility in binary choice where one outcome is predominantly preferred over the other. We find that when the frequently selected (“advantaged”) alternative is framed as an inaction, its choice share decreases, but that when the infrequently selected (“disadvantaged”) alternative is framed as an inaction, its choice share increases. Finally, we discuss potential moderators of our effects. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.3013